Fazendas corporativas e espoliação no início do século XXI: o despontar dos novos senhores da terra na região do MATOPIBA - Raoni Fernandes Azerêdo; Marco Antonio Mitidieiro Junior (Confins)
This article analyzes the agribusiness regionalization process in MATOPIBA, which, unlike other fractions of the Brazilian territory, has the predominance of corporate farms in soybean agricultural expansion, with a strong presence and association with internationalized / financierized capital, land and labor outsourcing. We found a typology of seven groups of corporate farms operating in the region and the intense interrelationship between them, whose strategies of accumulation by spoliation are derived from production (agricultural producers), but also from speculation and financialization (agricultural real estate) or both.